The level of acceptance to be friend with LGBT / Ummi Hazwani Abdullah and Nur Alya Syafiqa Che Mohd Radin - Abdullah, Ummi Hazwani; Che Mohd Radin, Nur Alya Syafiqa (Faculty of Communication & Media Studies, 2018)
The acronym LGBT stands for lesbian, gay, bisexual, and transgender describes individuals in smaller communities whose violate of nature. This study is done in order to find the acceptance of LGBT among Malaysians. This study also will highlight the reaction of Malaysians towards LGBT. This study uses LGBT as a topic because it is a hot issues to be discuss around the world. The study involved 302 respondents, a selected through a purpose sampling technique involving society in Malaysia. A cross sectional survey and structured questionnaire were used for data collection. All variables were measured through scales previously used by other researchers. The sampling was based on results Raosoft software. Results of the indicated shows that the acceptance of LGBT among Malaysians is high M=(3.02).